Evaluación de un modelo de simulación de crecimiento aplicado a genotipos de soya (Glycine max. L. Merr) bajo condiciones tropicales - Rey, L; López, Y.; Jaramillo Valencia, Angélica M.; White, Jeffrey W. (1996)
The crop growth simulation model of soybean (Glycine max. (L) Merr) Soygro V5.42, was tested under tropical conditions, using experimental data from a field experiment in which two genotypes (Soyica P-33 and Soyica Ariari-1) with different growth habit, were growth under two plant densities, at the Palmira Research Centre of the Corporación Colombiana de Investigación Agropecuaria, located at 3º32Ž north latitude and 76º17Ž west longitude, on a Mollison soil classified as Isohyperterthermic Aquic Hapludoll. Thirteen genetic coefficients were calibrated and showed sensitivity to the model. The validation of the model was made using previous experimental data from the same genotypes. The narrow line observed vs. predicted seed yields was close to the 1:1 slope, indicating that, the simulating was not skewed. Thus, the model explained well the variation due to planting dates and plant spatial distribution in the field. The simulation of planting dates effects in relation to climatic variation at three different soybean production regions, is in agreement with the traditional planting dates used by the soybean growers of Colombia.